2012
DOI: 10.1017/jgc.2012.27
|View full text |Cite
|
Sign up to set email alerts
|

The Invisibility of Covert Bullying Among Students: Challenges for School Intervention

Abstract: Covert bullying behaviours are at least as distressing for young people as overt forms of bullying, but often remain unnoticed or unacknowledged by adults. This invisibility is increased in schools by inattention to covert bullying in policy and practice, and limited staff understanding and skill to address covert behaviours. These factors can lead to a school culture that appears to tolerate and thus inadvertently encourages covert bullying. This study explores these dynamics in Australian primary and seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…The studies identified in Table 1 were conducted in the UK (n = 3) (Betts & Spenser, 2015;Boulton et al, 2014;Monks, Mahdavi, & Rix 2016), USA (n = 3) (Pelfrey & Weber, 2015;Stauffer et al, 2012;Styron et al, 2016) and Canada (n = 3) (Cassidy, Brown, & Jackson, 2012;Li, 2008;Ryan, Kariuki, & Yilmaz, 2011). The other studies identified represented Australia (n = 2) ( Barnes et al, 2012;Compton, Campbell, & Mergler, 2014), Turkey (n = 2) (Sezer, Yilmaz, & Yilmaz, 2015;Yilmaz, 2010) and Belgium (n = 2) (DeSmet et al, 2015;Vandebosch, Poels, & Deboutte, 2014), with one study each representing Lithuania (Baraldsnes, 2015), Israel (Eden, Heiman, & Olenik-Shemesh, 2013), New Zealand (Green et al, 2016), Taiwan (Republic of China) (Huang & Chou, 2013), and Northern Ireland and the Republic of Ireland (Purdy & Mc Guckin, 2015). Thirteen of the twenty studies utilised a survey methodology, with four taking a qualitative approach through focus groups (Betts & Spenser, 2015;Compton, Campbell, & Mergler, 2014;Monks, Mahdavi, & Rix, 2016) or interviews (Pelfrey & Weber, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies identified in Table 1 were conducted in the UK (n = 3) (Betts & Spenser, 2015;Boulton et al, 2014;Monks, Mahdavi, & Rix 2016), USA (n = 3) (Pelfrey & Weber, 2015;Stauffer et al, 2012;Styron et al, 2016) and Canada (n = 3) (Cassidy, Brown, & Jackson, 2012;Li, 2008;Ryan, Kariuki, & Yilmaz, 2011). The other studies identified represented Australia (n = 2) ( Barnes et al, 2012;Compton, Campbell, & Mergler, 2014), Turkey (n = 2) (Sezer, Yilmaz, & Yilmaz, 2015;Yilmaz, 2010) and Belgium (n = 2) (DeSmet et al, 2015;Vandebosch, Poels, & Deboutte, 2014), with one study each representing Lithuania (Baraldsnes, 2015), Israel (Eden, Heiman, & Olenik-Shemesh, 2013), New Zealand (Green et al, 2016), Taiwan (Republic of China) (Huang & Chou, 2013), and Northern Ireland and the Republic of Ireland (Purdy & Mc Guckin, 2015). Thirteen of the twenty studies utilised a survey methodology, with four taking a qualitative approach through focus groups (Betts & Spenser, 2015;Compton, Campbell, & Mergler, 2014;Monks, Mahdavi, & Rix, 2016) or interviews (Pelfrey & Weber, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
“…While this may suggest teachers have a good awareness concerning different types of cyberbullying within the school, it is important to note this is not generalisable for all teachers' perspectives. Teaching experience has been closely related to cyberbullying identification (Barnes et al, 2012), and so future investigations should examine the influence of peer-mentoring between experienced teachers and prospective candidates.…”
Section: Cyberbullying Characteristics and Student Involvementmentioning
confidence: 99%
“…Effectively responding to student bullying behaviours can be a significant source of stress for many teachers (Barnes et al, 2012). This paper provides an insight into what preservice teachers, know, think and are prepared for when graduating from their studies and moving into the classroom, to help empower both pre-service teachers and the schools they will work in to most effectively prevent, identify and respond to student bullying behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Information can be difficult to remove from the Internet and is often visible to a large online audience. Moreover, most Australian teachers have received no training and feel unskilled to address cyberbullying with their students (Barnes et al, ). This is problematic given that self‐efficacy to address bullying is associated with a greater likelihood of intervening effectively (Bradshaw, Sawyer, & O'Brennan, ).…”
Section: Introductionmentioning
confidence: 99%